What is the Concept of Negative Categories? (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The study deals with the influence and impact of negative emotions, thoughts, and experiences on individuals and society. It analyzes topics such as the psychology of negativity, the effects of negative thinking on mental health, the role of negative emotions in decision-making, and strategies for coping with negativity.